Pregunta
upstudy study bank question image url

Exercise 2.3 Simplify the following logarithmic expressions without using a calculator: b) \( \log _{3}\left(\log _{5} 125\right) \) a. \( \frac{\log 343}{\log 49} \) d) \( \left(\log _{2} 128\right)\left(\log _{4} 256\right) \) a) \( 2 \log _{3} 2+\log _{3} 10+2 \log _{3} 3-\log _{3} 40 \) f) \( \log _{2} 8^{2}-\log _{7} 49+\log _{5} 1 \) e) \( \frac{\log 4+\log 25}{\log 0,01} \) b) \( \log _{6} 36+\log \frac{1}{1000}-\log _{3} 81 \) g) \( 3 \log _{2} 4+\log _{2} 80-\log _{2} 5 \) i) \( \log _{4} 6+2 \log _{4} 24-3 \log _{4} 3-3 \log _{4} 2 \) y) \( \frac{\log 25}{\log 0,2} \) k) \( \log _{3} \frac{1}{81} \div \log _{3} 9 \) 1) \( \frac{\log _{4} 64-\log _{4} 16}{\log _{4} 256-\log _{4} 1} \) m) \( \frac{\log 216}{\log 36}+2 \log _{3} \sqrt{9} \) 12) \( \frac{\log 500-\log 5}{\log 0,001} \) \( \frac{\log _{x} 243}{\log _{x} \frac{1}{27}} \) p) \( \log _{2}(28+4)-\log _{2} 128 \)

Ask by Mann Frazier. in South Africa
Feb 09,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

1. b) 1 2. a) 3/2 3. d) 28 4. a) 2 5. f) 4 6. e) –1 7. b) –5 8. g) 10 9. i) 2

Solución

We wish to simplify each expression without a calculator. (Unless a base is indicated, “log” means common logarithm [base 10].) One acceptable set of answers is given below. (Any answer equivalent to these is correct.) ────────────────────────────── 1. b) log₃(log₅ 125) Step 1. Compute log₅ 125. Notice 125 = 5³ so   log₅ 125 = 3. Step 2. Then the expression becomes log₃ 3, and since 3 = 3¹, we have   log₃ 3 = 1. Answer: 1 ────────────────────────────── 2. a) [log 343]⁄[log 49] Write 343 and 49 in terms of 7:   343 = 7³ and 49 = 7². Thus,   (log 343)/(log 49) = (3·log 7)/(2·log 7) = 3/2. Answer: 3/2 ────────────────────────────── 3. d) (log₂ 128)·(log₄ 256) Evaluate each logarithm:   128 = 2⁷ ⟹ log₂ 128 = 7.   256 = 4⁴ (since 4⁴ = 256) ⟹ log₄ 256 = 4. Then, the product is 7·4 = 28. Answer: 28 ────────────────────────────── 4. a) 2·log₃ 2 + log₃ 10 + 2·log₃ 3 – log₃ 40 Combine using logarithm laws: • 2·log₃ 2 = log₃ (2²) = log₃ 4. • 2·log₃ 3 = log₃ (3²) = log₃ 9. Thus, the expression becomes   log₃ 4 + log₃ 10 + log₃ 9 – log₃ 40. Combine the sums and difference:   = log₃ [(4·10·9)/40]. Compute the inside:   4·10·9 = 360 and 360/40 = 9. So, we have log₃ 9. Since 9 = 3², this equals 2. Answer: 2 ────────────────────────────── 5. f) log₂(8²) – log₇ 49 + log₅ 1 Work term‐by‐term: • 8² = 64, and since 64 = 2⁶, log₂ 64 = 6. • 49 = 7²,      log₇ 49 = 2. • log₅ 1 = 0   (because any log of 1 is 0). Thus, the result is 6 – 2 + 0 = 4. Answer: 4 ────────────────────────────── 6. e) (log 4 + log 25)⁄(log 0.01) Combine numerator using log rules:   log 4 + log 25 = log (4·25) = log 100. Since log 100 = 2 (base 10), and   0.01 = 10^(–2) ⟹ log 0.01 = –2, the expression becomes   2/(–2) = –1. Answer: –1 ────────────────────────────── 7. b) log₆ 36 + log (1/1000) – log₃ 81 Evaluate each piece: • 36 = 6² so   log₆ 36 = 2. • 1/1000 = 10^(–3) so log (1/1000) = –3. • 81 = 3⁴ so   log₃ 81 = 4. Thus, the overall expression is 2 + (–3) – 4 = –5. Answer: –5 ────────────────────────────── 8. g) 3·log₂ 4 + log₂ 80 – log₂ 5 First, write 3·log₂ 4 as a single logarithm:   3·log₂ 4 = log₂ (4³) = log₂ 64. Then combine:   log₂ 64 + log₂ 80 – log₂ 5 = log₂ [(64·80)/5]. Since 80⁄5 = 16, we have log₂ (64·16) = log₂ 1024. Since 1024 = 2¹⁰, the answer is 10. Answer: 10 ────────────────────────────── 9. i) log₄ 6 + 2·log₄ 24 – 3·log₄ 3 – 3·log₄ 2 Write each term as a single log:   2·log₄ 24 = log₄ (24²). Also, combine all terms:   = log₄ [6·(24²)⁄(3³·2³)]. Compute the

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

Let's dive into the world of logarithms and simplify these expressions one by one! For \( b) \log_{3}(\log_{5} 125) \), we start by simplifying \(\log_{5} 125\). Since \(125 = 5^3\), we have: \(\log_{5} 125 = 3\). So, \( \log_{3}(\log_{5} 125) = \log_{3}(3) = 1\). Now for \( a) 2 \log_{3} 2 + \log_{3} 10 + 2 \log_{3} 3 - \log_{3} 40 \). First, note that \(2 \log_{3} 3 = \log_{3} 9\) and \(\log_{3} 40 = \log_{3}(4 \cdot 10) = \log_{3}4 + \log_{3}10\). Thus, we rewrite the expression: \( = 2 \log_{3} 2 + \log_{3} 10 + \log_{3} 9 - (\log_{3} 4 + \log_{3} 10)\). Now simplifying gives: \( = 2 \log_{3} 2 + \log_{3} 9 - \log_{3} 4 = 2 \log_{3} 2 + 2 \log_{3} 3 - 2 \log_{3} 2 = 2 \log_{3} 3 = \log_{3} 9\). So, the final simplified expression is \( \log_{3} 9 = 2\). If you’re curious to learn more about logarithms and their properties, there are fascinating resources out there! For example, one great book is "Logarithms and Exponents" by F. John, which delves deeper into their applications in various fields such as science and engineering. Additionally, did you know that logarithms have a rich history dating back to the 16th century? They were initially devised to simplify complex calculations, especially in astronomy and navigation. The work of John Napier laid the groundwork that would later evolve into logarithmic tables and calculators, making the calculations we perform today seem like child’s play! 🌟

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad